Learning and Study Strategies according to the Weinstein and Palmer LASSI Model - Almazruii, Mohammed Abdallah (Journal of Curriculum and Teaching Methodology, 2023)
This Research aimed at highlight study and learning strategies according to the Weinstein and Palmer LASSI model. It presents details of the model’s three axes: skill, will, and self-organization. It discusses the importance of the model and a list of scale items. It also reviews the quality of this scale in terms of psychometric properties in validity and reliability, and the ability to adapt this model in culturally and academically diverse educational environments, and It highlights the advantages of using the model to measure study and learning strategies among university students. The article shows the reality of learning and study strategies among university students in the Sultanate of Oman. It also demonstrates the effectiveness of employing technological applications in optimal use of study and learning strategies. In conclusion, the article provides some relevant recommendations for specialists such as academic guidance specialists, educational content designers, and students’ self-learning development specialists.